APLIKASI PERLAKUAN PERMUKAAN TANAH DAN JENIS BAHAN ORGANIK TERHADAP INDEKS PERTUMBUHAN TANAMAN CABE RAWIT - Muhammad Hatta (Jurnal Floratek, 2011)
This study was aimed at determining effects of soil surface treatments and organic matter types, as well as interactions between the two treatments on growth of cayenne pepper. The results showed that there were significant interactions between soil surface treatments and organic material types on plant growth of cayenne pepper at age of 5 weeks after planting.  Surface treatments affected plant growth However, the soil surface treatments were influenced by types of organic matters given in the soil.  On organic matter in the form of compost, the best growth was found on recycled newspaper mulch placed on soil surface. Conversely, on organic matter in the form of pieces of recycled newspaper, mulch of recycled newspapers gave the worst growth.  Organic matters also affected plant growth. However, treatment of organic matter was also influenced by soil surface treatments. On the surface soil compaction treatment, the best growth was obtained at compost. On treatment of newspaper mulch, the best growth was also obtained at the type of compost. In contrast, on the untreated soil surface, the best growth was found at the type of organic matter made of the pieces of recycled newspaper.